Bahia de Minas: o carnaval de Itabirito (MG) de 1990 até 2010 - Marcelle Rodrigues Silva (2017)
The carnival is a festive cultural practice, a place to experience leisure. The carnival of Itabirito, which receives the city residents and visitors from other cities of Minas, other Brazilian states and even from abroad, is organized by the City Hall. Throughout the years, the carnival was constituted by different manifestations, like corso parades, carnival blocks, and balls in the social clubs, practices that sometimes were in evidence sometimes not. In the 1990s, the party acquired new characteristics given mainly by the presence of sonorized blocks and electric trios, which started to take over the streets of the city during the party. This work had as objective the study of the configuration of the carnival of Itabirito between 1990 and 2010, seeking to understand its constitution (organization, spaces reserved for the event, attractions, investments and collection), economic and social relevance to the municipality, and the impacts of tourism on the party. From a historiographic approach, grounded on the history of the present, were analyzed 295 articles about the carnival of Itabirito, found in 16 newspaper titles belonging to the Municipal Public Archive of Itabirito. We also used manuals; magazines and clippings of documents for the mayor found in this same collection, which dealt with the theme of this study, as well as Itabirito's memorialist books and decrees published by the Itabirito Municipal Council that regulated the party. In this period, the carnival of Itabirito was marked by changes, mirroring the carnivals of Bahia, Rio de Janeiro and São Paulo, with the introduction of new musical rhythms such as axé, frevo, lambada and zumba; expansion of the geographic space reserved for the party due to the gradual public increase; rise in investments in infrastructure, hiring of personnel and financial contribution for the execution of the carnival; and changes in the program of the party that happened to be held almost exclusively in the city streets. One of the main actions taken by the municipal administration for the Itabirito carnival was the investment in tourism with the purpose of attracting more visitors to the party. It allocated such investment for the party's publicity, tourism infrastructure and partnerships with private enterprises. The presence of the visitors was welcome as they boosted the city's economy, but there were also the local merchants concerns regarding outside sellers. In turn, the City Hall feared the arrival of badger tourists to the city. The carnival of Itabirito was, therefore, a celebration marked by changes in its organization and its cultural manifestations, privileging the development of the tourist activity in the city. This work contributes to understanding the carnival of Itabirito and its relations with tourism in the city.